RELIABILITY INDICATORS OF PIPELINE WATER SUPPLY SYSTEMS FOR IRRIGATION CANALS (Intent Research Scientific Journal, 2025)
Having determined and evaluated the reliability indicators of the pipe water transmission facilities under construction during the period of use, it can be said that in order to increase reliability, it is necessary to clarify the characteristics of the joint operation of the structure and the ground and to further improve the methods of design, construction and use based on it.